2015
DOI: 10.1253/circj.cj-15-0502
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Influential Factors in Patients Implanted With a Left Ventricular Assist Device

Abstract: 2186KATO NP et al. Circulation JournalOfficial Journal of the Japanese Circulation Society http://www. j-circ.or.jpMeanwhile, there are no studies evaluating the difference in QOL between implantable and extracorporeal LVAD patients. The 2 types of LVADs provide similar results in terms of systemic circulation assist and cardiac unloading effect, but the effect on patients' QOL may differ.It is important to understand the factors associated with patients' QOL in order to outline management strategies for LVAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 27 publications
(16 reference statements)
1
31
0
Order By: Relevance
“…There were no significant differences in median baseline overall KCCQ (HM3: 40 [ [8][9][10][11][12][13][14][15], p ¼ 0.71) scores between HM3 and HMII devices. At 3 and 6 months of follow-up, patients demonstrated a significant improvement in KCCQ and in overall EQ-5D-5L scores compared with baseline (p o 0.001 for within-patient comparison, Figure 2).…”
Section: Hr-qol and Fcmentioning
confidence: 87%
See 1 more Smart Citation
“…There were no significant differences in median baseline overall KCCQ (HM3: 40 [ [8][9][10][11][12][13][14][15], p ¼ 0.71) scores between HM3 and HMII devices. At 3 and 6 months of follow-up, patients demonstrated a significant improvement in KCCQ and in overall EQ-5D-5L scores compared with baseline (p o 0.001 for within-patient comparison, Figure 2).…”
Section: Hr-qol and Fcmentioning
confidence: 87%
“…Clinical trials and registry studies have shown that most patients experience early and sustained improvements in FC and HR-QOL after LVAS implant. [6][7][8][9][10][11][12][13][14] However, an analysis of the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) by Arnold et al 6 found that 7.3% of patients alive on LVAS support have persistently poor QOL. Various correlates of reduced QOL gains have been identified, including female sex, age, baseline QOL scores, pre-operative anemia, non-cardiac comorbidities (diabetes, cancer), and the occurrence of complications after LVAS implant.…”
Section: Introductionmentioning
confidence: 99%
“…DT-LVAD has been shown to decrease mortality compared with medical therapy 1 , and can result in improved quality of life for many patients 1, 2 . While DT-LVAD can prolong survival for many patients with advanced HF, all patients will eventually die.…”
mentioning
confidence: 99%
“…From 2009 to 2012, the median risk-standardised 30-day readmission rate for HF was 23.0% 5. The overall implications of HF include a negative impact on patients’ quality of life, increased morbidity and mortality, and increased number of avoidable hospitalisations 6–8…”
Section: Introductionmentioning
confidence: 99%